2019
DOI: 10.1155/2019/1430624
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Offset Crack Interactions in Rock under Unloading Conditions

Abstract: Rock slopes contain numerous nonpenetrating intermittent joints which maintain stability under excavation disturbance. The tip interaction coefficient (IC) of parallel offset double cracks in a typical rock mass under unloading conditions was calculated in this study based on the superposition principle and fracture mechanics to determine the meso-influence law of intermittent joint interaction in the slope under the action of excavation. The influence of many factors on the said interaction was also analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…e composite coal-rock samples are essentially combinations of soft and hard phases, so their mechanical properties must be different from that of single coal or rock. Zhou et al studied the interaction of rock cracks under unloading conditions, which showed that the change of crack angle would weaken shear failure [6]. Qin et al studied the energy evolution and acoustic emission law of sandstone under unloading conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…e composite coal-rock samples are essentially combinations of soft and hard phases, so their mechanical properties must be different from that of single coal or rock. Zhou et al studied the interaction of rock cracks under unloading conditions, which showed that the change of crack angle would weaken shear failure [6]. Qin et al studied the energy evolution and acoustic emission law of sandstone under unloading conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many other valuable contributions to the literature. Zhou and Chen [10] studied the parallel crack interactions in rock under unloading conditions based on fracture mechanics and found that a smaller length of rock bridge or staggered distance between the cracks results in more severe and sensitive interactions at the crack tip. Zou et al [11] performed the research of cracking processes in a natural rock under dynamic loading conditions and found that only the antiwing and shear patches evolve into two symmetrical pairs of shear cracks, which result in the specimen failure under dynamic compression.…”
Section: Introductionmentioning
confidence: 99%